Presynaptic morphogenesis, active zone organization and structural plasticity in Drosophila. (April 2017) - Van Vactor, David; Sigrist, Stephan J
Highlights: Analysis using acute stimulation reveals that multiple signals are involved in activity-dependent synapse growth or remodeling in Drosophila. Addition of new synaptic boutons occurs through a series of steps that are each regulated by multiple intracellular and extracellular events. Abstract : Effective adaptation of neural circuit function to a changing environment requires many forms of plasticity. Among these, structural plasticity is one of the most durable, and is also an intrinsic part of the developmental logic for the formation and refinement of synaptic connectivity. Structural plasticity of presynaptic sites can involve the addition, remodeling, or removal of pre- and post-synaptic elements. However, this requires coordination of morphogenesis and assembly of the subcellular machinery for neurotransmitter release within the presynaptic neuron, as well as coordination of these events with the postsynaptic cell. While much progress has been made in revealing the cell biological mechanisms of postsynaptic structural plasticity, our understanding of presynaptic mechanisms is less complete.